anthocyanin1 of Petunia Encodes a Basic Helix-Loop-Helix Protein That Directly Activates Transcription of Structural Anthocyanin Genes - Spelt, Cornelis (American Society of Plant Physiologists, 2000)
The petunia loci anthocyanin1 (an1), an2, an4, and an11 are required for the transcription of anthocyanin biosynthetic genes in floral organs. The an2 and an11 loci were recently cloned and shown to encode a MYB-domain transcriptional activator and a cytosolic WD40 protein, respectively. Here, we report the isolation of an1 by transposon tagging. an1 encodes a new member of the basic helix-loop-helix family of transcription factors that is functionally and evolutionarily distinct from JAF13, the apparent petunia ortholog of maize RED1 and snapdragon DELILA. We provide genetic evidence that the transcription factors encoded by an1, an2, and an4 operate in an unexpectedly complex regulatory hierarchy. In leaves, ectopic expression of AN2 induces an1 expression, whereas in anthers, an1 expression depends on an4, encoding (or controlling) a MYB protein that is paralogous to AN2. Experiments with transgenic plants expressing a post-translationally controlled AN1–GLUCOCORTICOID RECEPTOR fusion protein indicated that independent of protein synthesis, AN1 directly activates the expression of the dfrA gene encoding the enzyme dihydroflavonol 4-reductase and of Pmyb27 encoding a MYB-domain protein of unknown function.